LOCAL AESTHETICS AND COMMODIFICATION: EFFORTS TO SELF-ACTUALIZE AND EXISTENCE IN THE GEDRUK DANCE ART OF THE SALEHO GROUP - Paimin; Lokanantasari, Ryndhu Puspita; Sendanatasa Kunthi Febiyani (Institut Seni Indoensia Surakarta, 2025)
The development of folk arts has generated diverse modes of performance and increasing complexity. This article examines the dynamics of aesthetics and commodification in tari Gedruk, a folk dance performed by the Saleho group in Boyolali, Central Java. Employing an ethnographic approach, the study explores how this community-based art group integrates local aesthetic values—particularly the concept of gayeng, which emphasizes festivity, spontaneity, and emotional engagement—with commercial strategies as a means of self-actualization and sustaining cultural presence. Gayeng serves as a primary aesthetic parameter, replacing classical standards and reflecting the ways in which aesthetics are experienced and interpreted by local audiences. What kind of aesthetics emerge in such a context? And how do they function within the logic of popular performance? In this framework, tari Gedruk becomes not only a form of cultural expression but also a commodified creative product that aligns with contemporary entertainment demands while preserving its indigenous values. Using the Saleho group as a case study, this article argues that local aesthetics and commodification are not necessarily oppositional, but can instead coexist and inform each other within the evolving landscape of folk performance. Ultimately, commodification here is not solely about generating material profit, but also a strategic response to ensure the continuity and vitality of the art itself. This reflects how traditional arts survive outside palace walls and institutional cultural systems.